2017
DOI: 10.1002/adma.201702375
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Bubble Domains and Topological Transitions in Ultrathin Ferroelectric Films

Abstract: Observation of a new type of nanoscale ferroelectric domains, termed as "bubble domains"-laterally confined spheroids of sub-10 nm size with local dipoles self-aligned in a direction opposite to the macroscopic polarization of a surrounding ferroelectric matrix-is reported. The bubble domains appear in ultrathin epitaxial PbZr Ti O /SrTiO /PbZr Ti O ferroelectric sandwich structures due to the interplay between charge and lattice degrees of freedom. The existence of the bubble domains is revealed by high-resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
121
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 136 publications
(129 citation statements)
references
References 49 publications
5
121
0
3
Order By: Relevance
“…Previously, we have shown that even under a very weak AC field the bubble domains can easily morph into classical cylindrical domains and eventually merge to form a mesoscale labyrinthine polydomain network . This transition from the bubble domain to the cylindrical domain state under electrical bias manifests a polarization rotation process, which results in a significant enhancement of the electromechanical response.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Previously, we have shown that even under a very weak AC field the bubble domains can easily morph into classical cylindrical domains and eventually merge to form a mesoscale labyrinthine polydomain network . This transition from the bubble domain to the cylindrical domain state under electrical bias manifests a polarization rotation process, which results in a significant enhancement of the electromechanical response.…”
Section: Resultsmentioning
confidence: 92%
“…The crystallographic details of (001)‐oriented epitaxial PZT/STO/PZT sandwich films on La 0.67 Sr 0.33 MnO 3 (LSMO) buffered STO substrate used here can be found elsewhere . For this study, we chose PZT layer fixed at 7 unit cells (u.c.)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The recent discovery of novel domain patterns or complex domain arrangements in nanoscale ferroelectrics has regenerated much attention to the search for phases that do not exist in the parent bulk materials . Structures such as vortex pairs, super‐tetragonal phase, and polar skyrmions have been experimentally reported . In essence, the formation of ferroelectric domain structures strongly relies on the balance between electrostatic and elastic energies which is sensitively affected by film thickness, substrate mismatch strain, depolarization field, cooling rate, etc .…”
mentioning
confidence: 99%